2015
DOI: 10.1159/000440953
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Strength, Function and Heart Autonomic Regulation System Recovery at the Sub-Acute Stage Post Stroke

Abstract: Background: To compare the rate of recovery of motor and functional ability and heart rate variability (HRV) parameters during the inpatient rehabilitation period. Summary: Twenty-three patients post first stroke at the sub-acute phase underwent motor and functional ability and HRV assessments 20 and 50 days after the event. A significant improvement was noted in motor and functional ability performance during the follow-up period, while no such change was noted in the HRV parameters. Key Messages: Patients po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The examined muscle groups of the lower limbs (i.e. hip flexors, knee flexors, knee extensors and ankle dorsiflexors), measured within the early subacute stage, showed a significant increase in muscle strength on the paretic side with moderate, positive effect sizes (p < 0.05, g H : 0.34-0.70) (31,34,62,63).…”
Section: Muscle Strengthmentioning
confidence: 97%
See 3 more Smart Citations
“…The examined muscle groups of the lower limbs (i.e. hip flexors, knee flexors, knee extensors and ankle dorsiflexors), measured within the early subacute stage, showed a significant increase in muscle strength on the paretic side with moderate, positive effect sizes (p < 0.05, g H : 0.34-0.70) (31,34,62,63).…”
Section: Muscle Strengthmentioning
confidence: 97%
“…Concerning the non-paretic side, muscle strength of the lower limbs significantly increased in the hip flexors (p < 0.05, g H : 0.24-0.25) and ankle dorsiflexors (p < 0.05, g H : 0.26-0.31) (31,34), whilst studies that investigated the knee extensors and flexors reported mixed results (p < 0.001 to p > 0.05, g H : 0.06-0.28) (31,34,49,62,63).…”
Section: Muscle Strengthmentioning
confidence: 99%
See 2 more Smart Citations